2000
DOI: 10.1038/sj.mp.4000788
|View full text |Cite
|
Sign up to set email alerts
|

No association or linkage between polymorphisms in the genes encoding cholecystokinin and the cholecystokinin B receptor and panic disorder

Abstract: Growing animal data implicate cholecystokinin in the regulation of anxiety, while human clinical research confirms the role of cholecystokinin in the provocation of panic attacks. Antipanic medications suppress the ability of cholecystokinin to induce panic attacks, and may alter the expression of the cholecystokinin gene. Thus, there is increased interest in understanding the molecular genetic component of these observations. Recent association studies using persons with panic disorder described some associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 40 publications
(43 reference statements)
3
38
3
Order By: Relevance
“…However, even if this is a true linkage signal, the source of the signal could plausibly be one of the other genes in this map region. A previous investigation suggested genetic association between CCKBR and PD [Kennedy et al, 1999]; however, Hamilton et al [2001] found neither association or linkage of CCKRB to PD, using an short tandem repeat (STR) polymorphism. PD and agoraphobia have often been conceptualized clinically as parts of a severity continuum, with agoraphobia developing at least partly as a response to situational panic attacks, symptomatic of increasing severity of the disorder.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, even if this is a true linkage signal, the source of the signal could plausibly be one of the other genes in this map region. A previous investigation suggested genetic association between CCKBR and PD [Kennedy et al, 1999]; however, Hamilton et al [2001] found neither association or linkage of CCKRB to PD, using an short tandem repeat (STR) polymorphism. PD and agoraphobia have often been conceptualized clinically as parts of a severity continuum, with agoraphobia developing at least partly as a response to situational panic attacks, symptomatic of increasing severity of the disorder.…”
Section: Discussionmentioning
confidence: 95%
“…Neither of the initial two genome scan reports [Knowles et al, 1998;Crowe et al, 2001] reported use of a marker at CCKBR, which was the site of our maximum LOD score. However, Hamilton et al [2001] recently reported negative linkage results in the Columbia pedigree series using a different CCKBR marker. Also, our study differed in recruitment strategy from the others in that our focus was not exclusively on PD.…”
Section: Discussionmentioning
confidence: 95%
“…Its heritability is estimated to be between 0.41 and 0.54 [Hettema et al, 2001]. A number of linkage and candidate gene association studies have been published for panic disorder [Hamilton et al, 2001;Sen et al, 2004;Van West and Claes, 2004;Cheng et al, 2006;Zeggini et al, 2007]. While numerous positive candidate gene associations and several linkage loci have been reported, only few of them have been replicated so far [Deckert et al, 1998[Deckert et al, , 1999Hamilton et al, 2002;Hosing et al, 2004;Peters et al, 2004;Domschke et al, 2007].…”
mentioning
confidence: 96%
“…SNPs were detected using fluorescence polarization, a technique that distinguishes the polymorphic base of an SNP by the template-directed incorporation of a dye-labeled dideoxynucleotide onto an oligonucleotide primer that anneals just 5 0 to the polymorphic base (Chen et al, 1999). This homogenous reaction was performed in three stages (Hamilton et al, 2001). Briefly, in the first step, PCR reactions of 5 ml containing 200 nM of the forward and reverse primers ( primers and deoxynucleotides in the PCR products were then degraded by adding a 5 ml solution of 1 U of shrimp alkaline phosphatase (Roche, Indianapolis), 0.5 U of Escherichia coli Exonuclease I (USB, Cleveland), 5mM MgCl 2 , and 50mM Tris-HCl (pH 8.5).…”
Section: Dna Analysismentioning
confidence: 99%